2020
DOI: 10.1167/iovs.61.10.6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Macular Curvature and Common Causative Genes of Retinitis Pigmentosa in Japanese Patients

Abstract: PURPOSE. To determine the relationship between the macular curvature and the causative genes of retinitis pigmentosa (RP). METHODS. We examined the medical records of the right eyes of 65 cases with RP (31 men and 34 women; average age, 47.6 years). There were 31 cases with the EYS variants, 11 cases with the USH2A variants, six cases with the RPGR variants, 13 cases with the RP1 variants, and four cases with the RP1L1 variants. The mean curvature of Bruch's membrane was calculated within 6 mm of the fovea as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The protein includes three regions: i) a large extracellular region with a signal peptide, a laminin N-terminal, 10 laminin epidermal growth factor-like domains, and 34 fibronectin type-III domains separated by 2 laminin G-like domains; ii) a transmembrane region; iii) a short intracellular region with a PDZ-binding motif at its C-terminal end ( Liu et al, 2007 ; Chen et al, 2014 ; Fu et al, 2020 ; Zhu et al, 2021 ). The USH2A variants, including missense, nonsense, duplications/insertions, deletions, indels, and splicing variants, spread throughout the 72 exons and their flanking intronic regions ( Aller et al, 2006 ; Koyanagi et al, 2020 ; Gao et al, 2021 ). Genotype-phenotype correlation has yet to be elucidated, while analyses based on some studies showed that patients with truncating variants may have more severe phenotypes, involving visual and auditory dysfunction ( Inaba et al, 2020 ; Meng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein includes three regions: i) a large extracellular region with a signal peptide, a laminin N-terminal, 10 laminin epidermal growth factor-like domains, and 34 fibronectin type-III domains separated by 2 laminin G-like domains; ii) a transmembrane region; iii) a short intracellular region with a PDZ-binding motif at its C-terminal end ( Liu et al, 2007 ; Chen et al, 2014 ; Fu et al, 2020 ; Zhu et al, 2021 ). The USH2A variants, including missense, nonsense, duplications/insertions, deletions, indels, and splicing variants, spread throughout the 72 exons and their flanking intronic regions ( Aller et al, 2006 ; Koyanagi et al, 2020 ; Gao et al, 2021 ). Genotype-phenotype correlation has yet to be elucidated, while analyses based on some studies showed that patients with truncating variants may have more severe phenotypes, involving visual and auditory dysfunction ( Inaba et al, 2020 ; Meng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has wide phenotypic and genetic heterogeneity with numerous gene defects ( Ávila-Fernández et al, 2010 ; Gao et al, 2019 ; Karali et al, 2019 ). The disorder is typically characterized by progressive degeneration of rod photoreceptors, cone photoreceptors, and retinal pigment epithelium, leading to night blindness, restricted peripheral vision (tunnel vision), and reduction of central vision ( Hartong et al, 2006 ; Verbakel et al, 2018 ; Koyanagi et al, 2020 ). The estimated prevalence of the disorder is about 0.025%, and there are more than 1.5 million reported patients worldwide ( de Castro-Miró et al, 2014 ; Menghini et al, 2020 ; Sharon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EZ width was defined as the distance between the temporal and nasal borders on the horizontal image or the superior and inferior borders on the vertical image of the EZ, where the EZ line disappeared. If the entire length of the EZ line exceeded the size of the OCT image, the borders of the EZ were set to be those of the OCT image [ 13 ]. In addition to the horizontal and vertical EZ widths, which were acquired from the horizontal and vertical OCT images, respectively, the average EZ width was calculated by averaging the horizontal and vertical EZ widths.…”
Section: Methodsmentioning
confidence: 99%
“…If the length of the EZ line exceeded the size of the OCT image, the borders of the EZ were considered to be those of the OCT image. 17 The EZ width measurements were performed twice by one observer (D.S. ), and the average values were recorded.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%